Analysis of Public Satisfaction towards Online Registration through the JKN Mobile Application in the Era of Health Service Digitalization - Zulaila Zulaila; Nanda Fadillah Darus; Fitriani Pramita Gurning (Lembaga Pengembangan Kinerja Dosen, 2025)
Advances in information technology have driven the transformation of health services towards digitalization, one of which is through the Mobile JKN application provided by BPJS Kesehatan. This study aims to analyze the level of satisfaction of the Medan City community with the online registration process using the Mobile JKN application. The research method used is a descriptive quantitative approach with a purposive sampling technique on 100 respondents who meet the criteria: domiciled in Medan City, aged over 17 years, and have used the Mobile JKN application. Data were collected through a closed questionnaire based on a Likert scale covering aspects of ease of use, speed of service, clarity of information, and general satisfaction. The results showed that the majority of respondents were satisfied with the ease of access and speed of registration through the application, although there were still technical obstacles and lack of information felt by some users. These findings can be the basis for improving the digitalization system of health services, especially in optimizing features and delivering information on the Mobile JKN application.